Fabrication of self-rolled Ni catalyst using water-soluble ceramics for NaBH4 dehydrogenation - Shin, Hojun; Park, Sang Yeop; Megersa, Daba Deme; Bae, Ji Kwon; Cho, In Sun; Yu, Hak Ki (International Journal of Hydrogen Energy, 2024)
This study explores the use of roll-up nickel films as catalysts for the dehydrogenation of sodium borohydride (NaBH4). The proposed structure, consisting of a 345-nm-thick Ni film and a 100-nm-thick sacrificial layer, is naturally rolled-up due to thermal stress induced by physical vapor deposition or additional heating. The catalytic performance was evaluated using the water displacement method, and it was found that a three-layer stacked structure using amorphous MoO3 as the sacrificial layer showed maximum efficiency. The stability of the structure was maintained even after repeated use, and surface analysis by X-ray photoelectron spectroscopy revealed the presence of Mo component that accelerates the rate of hydrolysis. Zeta potential and Kelvin probe force microscopy analysis further revealed that the amount of surface electrons of the Ni catalyst can be changed according to the sacrificial layer used. Based on these findings, MoO3/Ni/MoO3 and layered structures were found to have excellent catalytic performance. Importantly, the wafer can be reused, and the catalytic efficiency is maintained even with a low-thickness nickel catalyst, suggesting the economic advantage. This study offers insights into the development of cost-effective and high-performance catalysts for hydrogen generation.
Keywords: Catalytic performance; NaBH4 dehydrogenation; Ni catalysts; Nickel film; Sacrificial layer; Self-rolled catalyst; Sodium borohydrides; Water soluble ceramic; Watersoluble; ]+ catalyst; MoO3; NaBH4 dehydrogenation; NaCl; Self-rolled catalyst; Water soluble ceramics